Characteristics of adult patients with chronic intestinal failure due to short bowel syndrome: An international multicenter survey. (October 2021) - Pironi, Loris; Steiger, Ezra; Joly, Francisca; Jeppesen, Palle B.; Wanten, Geert; Sasdelli, Anna S.; Chambrier, Cecile; Aimasso, Umberto; Mundi, Manpreet S.; Szczepanek, Kinga; Jukes, Amelia; Theilla, Miriam; et al.
Summary: Background and aims: The case-mix of patients with intestinal failure due to short bowel syndrome (SBS-IF) can differ among centres and may also be affected by the timeframe of data collection. Therefore, the ESPEN international multicenter cross-sectional survey was analyzed to compare the characteristics of SBS-IF cohorts collected within the same timeframe in different countries. Methods: The study included 1880 adult SBS-IF patients collected in 2015 by 65 centres from 22 countries. The demographic, nutritional, SBS type (end jejunostomy, SBS-J; jejuno-colic anastomosis, SBS-JC; jejunoileal anastomosis with an intact colon and ileocecal valve, SBS-JIC), underlying disease and intravenous supplementation (IVS) characteristics were analyzed. IVS was classified as fluid and electrolyte alone (FE) or parenteral nutrition admixture (PN). The mean daily IVS volume, calculated on a weekly basis, was categorized as <1, 1–2, 2–3 and >3 L/day. Results: In the entire group: 60.7% were females and SBS-J comprised 60% of cases, while mesenteric ischaemia (MI) and Crohn' disease (CD) were the main underlying diseases. IVS dependency was longer than 3 years in around 50% of cases; IVS was infused ≥5 days/week in 75% and FE in 10% of cases. Within the SBS-IF cohort: CD was twice and thrice more frequent in SBS-J than SBS-JC and SBS-JIC, respectively, while MI was more frequent in SBS-JC and SBS-JIC. Within countries: SBS-J represented 75% or more of patients in UK and Denmark and 50-60% in the other countries, except Poland where SBS-JC prevailed. CD was the main underlying disease in UK, USA, Denmark and The Netherlands, while MI prevailed in France, Italy and Poland. Conclusions: SBS-IF type is primarily determined by the underlying disease, with significant variation between countries. These novel data will be useful for planning and managing both clinical activity and research studies on SBS.